Policies, strategies and prospects of research in oral health in Africa : Delphi Method, 2012-2013 - (:unkn) unknown (My University, 2014)
This work is a contribution to the strengthening of research capacity and the identification of strategies and opportunities to promote better research in oral health in Africa through the filing of the notice of a panel of experts at a Delphi consultation. This especially as systems oral health and scientific knowledge evolves rapidly. However, the African continent is facing many challenges, including the burden of oral diseases and the needs of populations that are huge. To meet these challenges care and ask actions effective public health policy makers need tools, skills and information to assess and monitor health needs, choose intervention strategies, policy options appropriate for the design of their own circumstances and improve system performance oral care. In this context, it is necessary to develop a coherent policy approach to oral health in the African Region, but this implies a better knowledge of the situation. For the advancement of Africa depends on its ability to generate, adapt and use scientific knowledge to meet local needs in health and development. That is why there is an urgent need to build the next generation of African scientists. Universities should promote and support research and training so that students are exposed to research and be taught by researchers throughout their courses. The collection of data on oral health is essential to get an accurate picture of the situation in Africa and to measure progress. Thus the objective of this research is to produce the opinion of a panel of experts on various items at a Delphi consultation two phases. In order to assess the current state of research, identify strategies to promote better research in oral health in Africa and prospects for its development. Analyzes give priorities to focus on the actions and involve a number of recommendations to strengthen and promote the capacity of research in oral health. Ultimately, we must promote a culture of research in national programs
Keywords: African Research